Pengaruh Struktur Modal, Ukuran Perusahaan, Likuiditas dan Intellectual Capital Terhadap Profitabilitas Pada Perusahaan Manufaktur Di Bursa Efek Indonesia Tahun 2017-2020 - Surbakti, Santi Betseba Br; Hidayat, Taufik (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
The purpose of this study was to assess the achievement of the company's business operating performance and to determine the effect of capital structure, company size, liquidity and intellectual capital on profitability in manufacturing companies on the Indonesia Stock Exchange in 2017-2020. Sample selection using purposive sampling method. Based on the predetermined criteria, a sample of 36 companies was obtained, so that the data obtained were 144. The data analysis techniques used were descriptive statistical analysis, classical assumption test, multiple linear regression analysis, hypothesis testing, and coefficient of determination. The results showed that partially capital structure and intellectual capital had a significant effect on profitability, while firm size and liquidity had no significant effect on profitability. Simultaneously, capital structure, firm size, liquidity and intellectual capital have a significant effect on profitability.